Protective interlayer for trapping polysulfides and a conducting host for sulfur: dual role of candle soot carbon for the development of high performance lithium–sulfur batteries. Issue 9 (7th April 2021) - Bharti, Vikram K.; Gangadharan, Ananya; Kumar, S. Krishna; Pathak, Anil D.; Sharma, Chandra S.
Abstract : Candle soot was investigated as conducting host and inbuilt interlayer for lithium–sulfur batteries. The material showed outstanding electrochemical performance with a specific capacity of 667 mAh g −1 at 1C after 200 cycles. Abstract : The commercial realization of next-generation lithium–sulfur (Li–S) batteries is mainly hindered due to the unwanted lithium polysulfide shuttling and the insulating nature of the sulfur cathode. In the present work, we aim to overcome these critical challenges by the first-time usage of candle soot carbon as a conducting host as well as an inbuilt interlayer. The Li–S battery thus fabricated delivers an impressive capacity of 1182 mA h g −1 with 92% coulombic efficiency at 0.1C. This excellent electrochemical performance is further maintained in long cycling even at a higher C-rate (1C) and exhibits a capacity of 667 mA h g −1 after 200 cycles with coulombic efficiency ∼95% (an extremely slow capacity decay rate of 0.03% per cycle). Moreover, for a high-sulfur loading (4.5 mg cm −2 ) electrode the Li–S battery retains 61.3% of the initial capacity after cycling for 150 cycles at 2.0C. Further, to understand the functional mechanism of the carbon interlayer for anchoring lithium polysulfides, first principles calculations are performed based on density functional theory. To the best of our knowledge, this is the first such report on using inexpensive candle soot carbon as a cathode host and as an interlayer that results in outstanding electrochemical performance.